PENGARUH KOMITMEN AUDITOR TERHADAP KUALITAS AUDIT DENGAN AUDIT FEE SEBAGAI VARIABEL MODERASI - Nurfitri Elsya; Saswinda Permata Putri; Yulian Yanuardi; Haryono Umar (Lembaga Penelitian Universitas Trisakti, 2019)
This study aims to obtain evidence about the influence of auditor commitment to audit quality with an audit fee as a moderating variable. The population in this study was the auditor of KAP in Jakarta. The research sample used non probability sampling, namely in the form of convenience sampling KAP Auditors. The primary data collection method used is the questionnaire method. Data were analyzed using SPSS. The results of the study indicate that audits fee strengthen the positive influence of auditor commitment to audit quality.